Hepatocytes maintain greater fluorescent bile acid accumulation and greater sensitivity to drug‐induced cell death in three‐dimensional matrix culture - Murray, John W. (Physiol Rep, 2014)
Primary hepatocytes undergo phenotypic dedifferentiation upon isolation from liver that typically includes down regulation of uptake transporters and up regulation of efflux transporters. Culturing cells between layers of collagen in a three‐dimensional (3D) “sandwich” is reported to restore hepatic phenotype. This report examines how 3D culturing affects accumulation of fluorophores, the cytotoxic response to bile acids and drugs, and whether cell to cell differences in fluorescent anion accumulation correlate with differences in cytotoxicity. Hepatocytes were found to accumulate fluorescent bile acid (FBA) at significantly higher levels than the related fluorophores, carboxyfluorescein diacetate, (4.4‐fold), carboxyfluorescein succinimidyl ester (4.8‐fold), and fluorescein (30‐fold). In 2D culture, FBA accumulation decreased to background levels by 32 h, Hoechst nuclear accumulation strongly decreased, and nuclear diameter increased, indicative of an efflux phenotype. In 3D culture, FBA accumulation was maintained through 168 h but at 1/3 the original intensity. Cell to cell differences in accumulated FBA did not correlate with levels of liver zonal markers L‐FBAP (zone 1) or glutamine synthetase (zone 3). Cytotoxic response to hydrophobic bile acids, acetaminophen, and phalloidin was maintained in 3D culture, and cells with higher FBA accumulation showed 12–18% higher toxicity than the total population toward hydrophobic bile acids (P < 0.05). Long‐term imaging showed oscillations in the accumulation of FBA over periods of hours. Overall, the studies suggest that high accumulation of FBA can indicate the sensitivity of cultured hepatocytes to hydrophobic bile acids and other toxins.